The Impact of Cadmium Loading In Fe/Alumina Catalysts and Synthesis Temperature on Carbon Nanotubes Growth by Chemical Vapor Deposition Method - M. Karimi; A. Badiei; P. Zarabadi-poor (Journal of Sciences, Islamic Republic of Iran, 2015)
We evaluated the effect of Fe/Alumina Catalyst contained different Cadmium contents and two synthesis temperatures on producing carbon nanotubes by chemical vapor deposition of methane as a feedstock.  X-ray powder diffraction (XRD), N2 adsorption-desorption, scanning electron microscopy (SEM), transmission electron microscopy (TEM), Raman spectroscopy and Thermogravimetry analysis (TGA) were used for characterizing of synthesized catalysts and carbon nanotubes.  Raman spectrum confirmed the presence of carbon nanotubes. TGA showed larger deposited carbon nanotubes in certain cadmium contents and higher synthesis temperature of 950 °C. Based on morphological assessment in SEM images, the increase in cadmium content leads to the decrease in diameter of resulted carbon nanotubes